Addressing the Gap: Perspectives on Developing English for Specific Purposes Course Books for Business Management in Mongolia (International Journal of Scientific Research and Management (IJSRM), 2024)
This research paper explores the necessity for the development of English for Specific Purposes (ESP) course books tailored to the needs of professionals in Business Management in Mongolia. Despite the availability of English for Academic Purposes (EAP) books, there remains a significant gap in resources catering to the specific language requirements of professionals in this field. English teachers in Mongolia recognize the importance of ESP materials in enhancing language proficiency and employability among Business Management students. Drawing upon interviews and surveys with English teachers, this paper highlights the challenges faced due to the absence of relevant ESP course books and proposes of recommendations for their creation and implementation.